Preparation and Characteristics of a New Antibacterial Cotton Fiber Bonding a Gemini-type Quaternary Ammonium Salt (Journal of Fiber Bioengineering and Informatics, 2008)
Two kinds of antibacterial cotton fiber (called as C_{14} and C_t) were prepared by bondinga gemini-type quaternary ammonium compound with a hydroxyl group in their spacer chain[1,5-bis(tetradecyl dimethyl ammonium iodide)-3- pentanol (called as DAP_{14})] and a mono-typequaternary ammonium compound [N-tetradecyldimethyl (3-trimethoxysilylpropyl) ammonium chloride(called as TMMP)], respectively, to the surface of cotton fiber using a coupling agent, tetraethoxysilane.Antibacterial characteristic of C_{14} was investigated comparatively with C_t. The experimental resultsindicated that C14 has higher antimicrobial activity than Ct against a broad range of microorganism,and average net bactericidal ratio against 15 strains of gram-negative, gram-positive bacteria andyeasts is 98.0% at 30&#176C and pH 6.0, which are 25.2 and 17.2 percentage point higher than those of C_tat treated time of 30min and 60min, respectively. Antibacterial activity of C_{14} was hardly influencedby environmental pH and temperature, and could not be removed from the surfaces of cotton fiber byrepeated washing with water.